(untitled) (Conference Zone, 2022)
In this article, as a result of the astronomical analysis of the geometric grid in the 16th century in India, it was determined that the map of 18 thousand worlds, that is, the cosmogram, was depicted, and it was compared with the map of 18 thousand worlds on the facade of the Ulughbek madrasa in Samarkand, and it was proved that there is harmony between the compositions.